Die roeping van die kerk - Beyers, Jaco (HTS teologiese studies, 2013)
The calling of the church. The question as to the calling of the church is not a practical but a theological issue. The church can easily keep itself busy with activities that seem important. However, are these activities really the motivation behind God’s call to the church? This article investigates the calling of the church as perceived from various relationships: church and world, church and culture and church and church. Church and world addresses the age-old argument that the church is in the world but not of the world. The church does have an obligation in the world towards politics and ecology. Another factor addressed in the article is the way in which the church copes with the secularised society. Regarding culture, the premise is that the church has no obligation towards culture. Culture merely becomes a means to an end for the church. The church wants to exist in a ‘free culture’, as Barth suggests. When discussing the calling of the church, an ecclesiology of some sorts is in fact presented. This is reflected in the paragraph on church and church. The church is always seen in relationship with God’s intention with the community He assembles. This might be the true calling of the church: to be a community that calls others to community.